Pelatihan Layanan Bimbingan dan Konseling Berparadigma Profetik Dalam Meningkatkan Aktualisasi Diri Siswa SMK: Penelitian - Abdul Hadi; Anifa Tuzzuhroh Nurbaiti; Eka Aryani (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Vocational high school students face several significant obstacles in their self-actualization and future planning process. First, a lack of self-confidence often discourages students from actively participating in various activities, which ultimately limits the development of their potential and ability to plan and achieve life goals. This community service project aims to test the effectiveness of prophetic guidance and counseling training in improving self-actualization in vocational high school students. This study implemented a group guidance approach with three main pillars of the prophetic paradigm: humanization, liberation, and transcendence. The community service method used quantitative analysis. The subjects were 40 students of SMKN 1 Pengasih. Data analysis used descriptive tests, the Shapiro-Wilk normality test, and a paired samples t-test. The community service results showed a significant increase in students' self-actualization scores after participating in the training. Thus, this community service program proves that prophetic guidance and counseling training is effective in improving self-actualization in vocational high school students. This prophetic approach is considered successful because it integrates modern psychology with spiritual values, thereby helping students develop holistically and overcome modern challenges.